2019
DOI: 10.3389/fphys.2019.00726
|View full text |Cite
|
Sign up to set email alerts
|

Eight Weeks of Plyometric Training Improves Ability to Change Direction and Dynamic Postural Control in Female Basketball Players

Abstract: The aim of this study was to examine the effects of 8 weeks of plyometric training on the ability to change direction and postural control in female basketball players. 25 national level female basketball players aged 18–27 years participated in the study. Volunteers were randomly assigned to an experimental group ( n = 13) who replaced a part of their standard regimen by plyometric training twice weekly for 8 weeks, and a control group ( n = 12) who continued thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 50 publications
7
50
0
1
Order By: Relevance
“…Similar to this study Benis et al observed that national female basketball players enhanced their scores on the Y balance test in both postero-medial and postero-lateral but not in the anterior plane following 8 weeks of biweekly bodyweight neuromuscular training [22]. But in contrast to this study Cherni et al reported significant improvement in the ability of static and dynamic postural control after 8 week plyometric training program [23]. Also, Myer et al reported that after 7 week of plyometric training high school female volleyball players decreased their medio-lateral center of pressure, despite the absence of change in the antero-posterior center of pressure [24].…”
Section: Discussionsupporting
confidence: 72%
“…Similar to this study Benis et al observed that national female basketball players enhanced their scores on the Y balance test in both postero-medial and postero-lateral but not in the anterior plane following 8 weeks of biweekly bodyweight neuromuscular training [22]. But in contrast to this study Cherni et al reported significant improvement in the ability of static and dynamic postural control after 8 week plyometric training program [23]. Also, Myer et al reported that after 7 week of plyometric training high school female volleyball players decreased their medio-lateral center of pressure, despite the absence of change in the antero-posterior center of pressure [24].…”
Section: Discussionsupporting
confidence: 72%
“…Others, also, have found no effects on balance from lower limb plyometrics alone. Thus, Hammami et al (2019) found no effects on static and dynamic balance after 9 weeks of plyometric training in U14 female handball players, and Meszler and Vaczi (2019) saw no effects after 7 weeks of plyometric training in female basketball players aged less than 17 years, although Cherni et al (2019) did report a significant improvement in the static balance test of adult female basketball players after plyometric training, and Benis et al (2016) noted improved postural control and lower-limb stability as assessed by the Y balance test when adult female basketball players undertook body-weight neuromuscular training.…”
Section: Discussionmentioning
confidence: 92%
“…It can be said that physical exercise is always a kind of physical activity, but physical activity is not necessarily physical exercise [ 19 ]. In particular, the term physical activity covers all muscle-induced bodily movements leading to an increase in energy expenditure above ∼1.0/1.5 MET (metabolic equivalent of task; 1 MET = 1 kcal (4184 kJ) • kg −1 • h −1 ) [ 17 , 18 , 20 , 21 , 22 , 23 , 24 ]. The term physical exercise covers specific, planned, and structured forms of physical activity [ 17 , 18 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the term physical activity covers all muscle-induced bodily movements leading to an increase in energy expenditure above ∼1.0/1.5 MET (metabolic equivalent of task; 1 MET = 1 kcal (4184 kJ) • kg −1 • h −1 ) [ 17 , 18 , 20 , 21 , 22 , 23 , 24 ]. The term physical exercise covers specific, planned, and structured forms of physical activity [ 17 , 18 , 20 , 21 , 22 , 23 , 24 ]. Furthermore, there is a distinction between acute physical exercise (i.e., a single bout) and chronic physical exercise (i.e., repeated bouts of acute exercises), where the latter could also be denoted as physical training when physical exercises (i) are conducted regularly in a planned, structured, and purposive manner and (ii) with the objective of increasing or, at least, maintaining the individual fitness and health status in one or multiple dimensions [ 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%